From kinetic to collective behavior in thermal transport on semiconductors and semiconductor nanostructures - de Tomas, Carla Mercedes; Cantarero, A.; Lopeandia, A.; Alvarez, F. (American Institute of Physics, 2014)
We present a model which deepens into the role that normal scattering has on the thermal conductivity in semiconductor bulk, micro, and nanoscale samples. Thermal conductivity as a function of the temperature undergoes a smooth transition from a kinetic to a collective regime that depends on the importance of normal scattering events. We demonstrate that in this transition, the key point to fit experimental data is changing the way to perform the average on the scattering rates. We apply the model to bulk Si with different isotopic compositions obtaining an accurate fit. Then we calculate the thermal conductivity of Si thin films and nanowires by only introducing the effective size as additional parameter. The model provides a better prediction of the thermal conductivity behavior valid for all temperatures and sizes above 30 nm with a single expression. Avoiding the introduction of confinement or quantum effects, the model permits to establish the limit of classical theories in the study of the thermal conductivity in nanoscopic systems. © 2014 AIP Publishing LLC.